Analisis Tingkat Kesehatan Bank Pada PT. BPR Tunas Artha Jaya Abadi - Mahardhika, Ginanjar Galang; Arisyahidin, Arisyahidin; Mutiara, Nisa (Otonomi, 2024)
Rural banks (BPR) have an important role in supporting the Indonesian economy through providing financial access for the public and micro, small, and medium enterprises. Bank’sHealth is one of the parameters on which the bank is trusted by the public, so the health factor is one of the important factors in managing the banking business. This study aims to analyze the Bank’s Health Level at BPR Tunas Artha Jaya Abadi using RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital). This research uses quantitative research with a descriptive approach and uses secondary data obtained by documentation as a method of searching for data.The results showed that the Bank's Health Level at PT. BPR Tunas Artha Jaya Abadi in terms of RGEC (Risk, Good Corporate Governance, Earnings, Capital) aspect in 2017-2022 has an average RGEC value of 86.67% or a Composite Rating (PK) predicate of 1.